The Impact of Childhood Abuse and Current Mental Health on Young Adult Intimate Relationship Functioning. Issue 22 (November 2017) - Tardif-Williams, Christine Y.; Tanaka, Masako; Boyle, Michael H.; MacMillan, Harriet L.
This study examines the association between childhood abuse and intimate relationship quality and attachment security in young adults. Data were drawn from the Ontario Child Health Study, a province-wide community-based survey that collected baseline data in 1983 from 3, 294 children (aged 4 to 16 years) and follow-up data in 2000/2001 (then aged 21 to 35 years). The sample comprised 1, 885 men and women who had completed questionnaires regarding retrospective accounts of childhood abuse and current relationship status in 2000/2001. Childhood physical and sexual abuse was assessed using the short form of the Childhood Experiences of Violence Questionnaire. It was hypothesized that childhood physical and sexual abuse would be associated with adult intimate relationship functioning, adjusting for childhood family and individual factors, and that these associations would be mediated by participants' current mental health. The analysis for intimate relationship quality showed that current mental health reduced the association between physical abuse and poor relationship quality (beta 0.09 (se 0.02) to 0.08 (0.02)) and between sexual abuse and this outcome to a non-significant level ((beta 0.07 (se 0.03) to 0.05 (0.03)). The analysis for adult attachment security showed that current mental health reduced the association between physical abuse and insecure attachment to a non-significant level (OR 1.33 (95% CI 1.02-1.76) to OR 1.31 (0.98-1.76)) and between sexual abuse and this outcome (OR 1.89 (1.36-2.65) to OR 1.74 (1.19-2.52)). The importance of current mental health functioning in accounting for continuity in intimate relationship functioning from childhood to young adulthood is discussed.